The Performance of Deep Neural Networks in Differentiating Chest X-Rays of COVID-19 Patients From Other Bacterial and Viral Pneumonias - Elgendi, Mohamed; Nasir, Muhammad Umer; Tang, Qunfeng; Fletcher, Richard Ribon; Howard, Newton; Menon, Carlo; Ward, Rabab; Parker, William; Nicolaou, Savvas (Frontiers in Medicine, 2020)
Chest radiography is a critical tool in the early detection, management planning and follow up evaluation of COVID-19 pneumonia; however, in smaller clinics around the world, there is a shortage of radiologists to analyze large number of examinations especially performed during a pandemic. Limited availability of high-resolution computed tomography and real time polymerase chain reaction in developing countries and regions of high patient turnover also emphasizes the importance of chest radiography as both a a screening and diagnostic tool. In this paper, we compare the performance of 17 available deep learning algorithms to help identify imaging features of COVID19 pneumonia. We utilize an existing diagnostic technology (chest radiography) and preexisting neural networks (DarkNet-19) to detect imaging features of COVID-19 pneumonia. Our approach eliminates the extra time and resources needed to develop new technology and associated algorithms, thus aiding the front-line heath care workers in the race against the COVID-19 pandemic. Our results show that DarkNet-19 is the optimal pretrained neural network for the detection of radiographic features of COVID-19 pneumonia, scoring an overall accuracy of 94.28% over 5,854 X-ray images. We also present a custom visualization of the results that can be used to highlight important visual biomarkers of the disease and disease progression.